Good governance, people's participation and NGOs - Mishra, S.N.; Mishra, Sweta (1998)
Following a discussion on conceptual issues relating to good governance and people's participation, the authors, in the light of provisions under 73rd and 74th amendments, discuss the possibilities and problems visualised for realising participation by masses at the district level. They visualise an effective role for NGOs in promoting good governance through exposing their functionaries to the process of training and capacity building to bridge the existing local community-administration gap. - Reproduced
Keywords: Community participation; Nongovernmental organizations; Public administration; Good governance